Ashab al-Kahf in the Writings of the Orientalist Johann Wolfgang von Goethe: A Semantic Study of the Intertextuality with Surah Al-Kahf: أصحاب الكهف في كتابات المستشرق يوهان فولفغانغ فون غوته: دراسة دلالية لألفاظ التناص مع سورة الكهف - Albshkar, Hajer; Ayad, Nahid; Alouzi, Khuloud; Masuwd, Mowafg; Abdulghani, Naser (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2024)
This study analyses how the poem